Recurrent vaginal prolapse in a postpartum river buffalo and its management - Yimer, Nurhusien; S. Z., Syamira; Yusoff, Rosnina; Haron, Abd Wahid; Kazhal, Sarsaifi; M.M., Bukar; Yap, K.C. (Thai Buffalo Association * Research Centre for Bioscience in Animal Production, 2016)
This article presents a case report based on a river buffalo cow with a history of recurrent vaginal prolapse following a normal parturition. After clinical examination, the buffalo was diagnosed with first grade vaginal prolapse. Following administration of epidural anesthesia (Lidocaine), the area of vulva was aseptically prepared and a modified boot-lace retention suture was applied using nylon tape to prevent recurrence of the prolapse. Because of a foul smell lochia detected and for prevention of further contamination, antibiotic was administered. The buffalo was also treated with anti-inflammatory drug and drugs useful to help muscle tonicity and retention of reproductive organs in place. Two weeks later suture was removed and the animal recovered successfully with no recurrence reported after that. Though vaginal prolapse in buffalo has been reported to be most common during last trimester of pregnancy or associated with dystocia, the present case shows that it can also occur following normal parturition.